Effects of different PEEP levels on respiratory mechanics and oxygenation after coronary artery bypass grafting - Borges,Daniel Lago (2013)
OBJECTIVE: To compare the effects of different levels of positive end-expiratory pressure on respiratory mechanics and oxygenation indexes in the immediate postoperative period of coronary artery bypass grafting. METHODS: Randomized clinical trial in which 136 patients underwent coronary artery bypass grafting between January 2011 and March 2012 were divided into three groups and admitted to mechanical ventilation with different positive end-expiratory pressure levels: Group A, 5 cmH2O (n=44), Group B, 8 cmH2O (n=47) and Group C, 10 cmH2O (n=45). Data about respiratory mechanics were obtained from mechanical ventilator monitor and oxygenation indexes from arterial blood gas samples, collected twenty minutes after intensive care unit admission. Patients with chronic obstructive pulmonary disease and patients submitted to off-pump, emergency or combined operations were not included. For statistical analysis, we used Kruskal-Wallis, G and Chi-square tests, considering results significant when P<0.05. RESULTS: Groups were homogeneous in terms of demographic, clinical and surgical variables. Patients ventilated with positive end-expiratory pressure of 10 cmH2O (Group C) had best compliance (P=0.04) and airway resistance values, this, however, without statistical significance. They also had best oxygenation indexes, with statistical difference in all analyzed variables, and lower frequency of hypoxemia (P=0.03). CONCLUSION: Higher levels of positive end-expiratory pressure in immediate postoperative period of coronary artery bypass grafting improved pulmonary compliance values and increased oxygenation indexes, resulting in lower frequency of hypoxemia.